Poly-Phytopharm Increases Act Score and Serum miR-126 Relative Expressions, and Decreases Blood Eosinophil Levels in Asthma Patients - I Dewa Putu Ardana; Susanthy Djajalaksana; Iin Noor Chozin; Alidha Nur Rakhmani (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2019)
Background: The levels of asthma control is an indicator of asthma management outcomes. A complex immunological mechanism influences it. We aimed to investigate the effect of Poly-Phytopharm on the asthma control tests (ACT) score, blood eosinophil levels, and miR-126 relative expressions in asthma patients. Methods: Quasi experimental method is used in 15 stable asthma patients who were not fully controlled at the pulmonary outpatient clinic of Dr. Saiful Anwar General Hospital Malang. Assessment of ACT score, blood eosinophil levels, and miR-126 relative expressions are carried out before and after supplementation of Poly-Phytopharm that consist of Nigella sativa 100 mg, Kleinhovia hospita 100 mg, Curcuma xanthorrhiza 75 mg, and Ophiocephalus striatus 100 mg extract, three times a day, two capsules respectively for 12 weeks. The ACT was scored by the investigator by direct questioning of patients, the blood eosinophil level was measured with blood analysis, and the relative expressions of miR-126 was detected with qPCR. Results: There were significant increase of ACT score (18.07±2.57 to 22.06±1.83, P=0.001), decrease in blood eosinophil levels (653.15±276.15 pg/mL to 460.66±202.04 pg/mL, P=0.038), and enhancement of serum miR-126 relative expressions (1.83±1.89 to 5.89±1.34, P=0.038). Conclusion: The administration of Poly-Phytopharm increases ACT score, decreases blood eosinophil levels and increases serum miR-126 relative expressions in not fully controlled stable asthma patients. (J Respir Indo. 2019; 39(4): 231-7)